CARBON EMISSIONS DISCLOSURE AND FIRM VALUE: DOES ENVIRONMENTAL PERFORMANCE MODERATE THIS RELATIONSHIP? - Hardiyansah, Mohammad; Agustini, Aisa Tri (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2021)
The objectives of this research is to examine the role of environmental performance in the relation between carbon emissions disclosure and firm value. A measurement tool using content analysis method to measure carbon emissions disclosure that adopts a checklist from the Carbon Disclosure Project (CDP). Firm value is proxies with Tobin's Q, while environmental performance is assessed based on the results of the environmental management performance appraisal program (PROPER). Sample of this study using 34 companies that listed on the Indonesian Sharia Stock Index (ISSI) from 2014 to 2019. Moderated regression analysis (MRA) is used to test the hypothesis. The results indicate the carbon emissions disclosure has a positive and significant effect on firm value. This research also found that there is an evidence that environmental performance can strengthen the relation of carbon emissions disclosure to firm value, due to the company's efforts by participating in the PROPER program is a form of corporate responsibility in an effort to reduce the impact of environmental damage arising from the company's operational activities which have been responded positively by investors.